Phenotypic aspects of oral strains of Candida albicans in children with down's syndrome - Ribeiro, E. L. (2006)
The aim of this article is to characterize the biological aspects of oral strains of C. albicans in children with Down's syndrome. These yeasts were analyzed as to their macromorphological and enzymatic aspects and were tested as to their in vitro susceptibility to antifungal drugs using broth microdilution to determine the minimum inhibitory concentration (MIC). The morphotyping revealed that all oral C. albicans isolates from children with Down's syndrome promoted the formation of fringes regardless of size, while the control group presented smaller fringes. All oral C. albicans strains produced proteinase, but those with phospholipolytic activity showed greater enzyme capacity in the test group. In vitro susceptibility showed that all oral C. albicans isolates were sensitive to the drugs used.